PERILAKU BULLYING PADA ANAK DAN REMAJA - Sugiariyanti, Sugiariyanti (Jurusan Psikologi, Fakultas Ilmu Pendidikan, Universitas Negeri Semarang, 2009)
Bullying is a common issue in elementary and secondary schools, but it presents a serious threat to a healthy development during the school career. Bullying in school is a pervasive social problem in which children exploit power imbalances in order to dominate and harm others physically, socially, or emotionally. Individual characteristics in a certain developmental stage affect their behavior, so the goal of this study is trying to describe bullying among children in elementary school and adolescents in school contexts Our objectives were to compare bullying among children in elementary schools and adolescents in high schools for the following: frequency and type of bullying; the location where the bullying occurs; percentages of children and adolescents who identified as bullies, victims, and bystanders in bullying events; children and adolescents knowledge at bullying. The sample of this study were children in elementary school Grade VI and adolescents in high school Grade III by cluster random sampling technique. The instruments were two types of questionnaires; the one with pictures was for children and the one without pictures was for adolescents samples. The results of this study described children and adolescents bullying in schools for the following: 1) Physically bullying was the most type of bullying that occurred in children. Verbal bullying was the most type of bullying that occurred in adolescents. 2) The location where the bullying occurred the most was the classroom either in children or adolescents. 3) Students who identified as bullies were 8% of the children samples and 5% if the adolescents samples. There was no difference percentage of students who identified as victims, it was 3% of the children samples and also 3% of the the adolescents samples. Students who identified as bystanders were 24% of the children and 22% of the adolescents samples. 4) The category of knowledge level at bullying in children samples were 70% at average, 25% at low and 5% at high. The category of knowledge level at bullying in adolescents samples were 90% at average, 5% at low and 5% at high.